Genetic divergence studies in finger millet (Eleusine coracana L. Gaertn.) genotypes - G. Bharathi1, K. Radhika1, N. Anuradha2, K. Jayalalitha3 and V. Srinivasa Rao4 (Electronic Journal of Plant Breeding, 2023)
The genetic divergence among 105 finger millet genotypes was estimated using Mahalanobis’ generalized distance using D2 statistics. All the genotypes were grouped into fourteen clusters using Tocher’s method. Cluster I was the largest comprising of maximum number of 30 genotypes followed by cluster II and VIII consisting of 22 genotypes each and cluster VI was aggregated with 21 genotypes. The remaining clusters III, IV, V, VII, IX, X, XI, XII, XIII and XIV were found to be solitary clusters. Among the characters studied grain protein content (32.6 %) contributed maximum to total variation followed by days to 50 % flowering (12.38 %) and grain iron content (9.18 %). Hybridization between genotypes of cluster XIII (VR 1122) with those of either cluster XI (IC0476229) or cluster XIV (FM 1918) with maximum inter cluster distance will be useful to obtain good hybrid vigour and desirable segregants.